2020
DOI: 10.51441/biomedica//biomedica/5-411
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal Outcome in Women with COVID-19 in a COVID Designated Hospital in Lahore, Pakistan

Abstract: <p><strong>Background and Objective:</strong> The pandemic caused by Coronavirus disease-2019 (COVID-19) is notably becoming similar to severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome viruses (MERS) for causing poor feto-maternal outcome. There is not much data available about COVID-19 during pregnancy in Pakistan therefore the objective of this study is to determine maternal and fetal outcome in pregnant women affected with COVID-19 and to find out frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…There is no difference in adverse pregnancy outcomes in terms of obstetric haemorrhage between SARS-Cov-2 positive and SARS-Cov-2 negative women admitted for delivery during pregnancy. However, Munir SI et al 4 observed that the prevalence of COVID-19 in pregnant women is not significantly different from that seen in the general population. In most cases, the outcome for the fetus and the mother is favourable, and there is no indication of vertical transmission in any of the new-borns.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…There is no difference in adverse pregnancy outcomes in terms of obstetric haemorrhage between SARS-Cov-2 positive and SARS-Cov-2 negative women admitted for delivery during pregnancy. However, Munir SI et al 4 observed that the prevalence of COVID-19 in pregnant women is not significantly different from that seen in the general population. In most cases, the outcome for the fetus and the mother is favourable, and there is no indication of vertical transmission in any of the new-borns.…”
Section: Resultsmentioning
confidence: 89%
“…COVID-19 clinical manifestations of COVID-19 are similar to those of other corona viruses, with symptoms including cough, fever, diarrhoea, headache, and myalgia. 4 The world has been changed in an unprecedented manner because of SARS-CoV-2, the novel strain of corona virus that causes COVID-19. The rapid universal spreading of SARS-CoV-2 may stipulate that the reproduction number of the virus, which is currently an accepted approximate, may be an underestimate because there are many asymptomatic carriers of the virus, and even though they are contagious, they are not detected by the public health surveillance systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Brazilian report showed that almost all of its participants wear protective equipment (Moreira and Jesus, 2013). On the other hand, a study conducted on a Pakistani dental hospital harbouring more than 200 employees demonstrated that none of its practitioners or waste disposal workers have protective equipment nor are vaccinated against HBV (Mushtaq and Iqbal, 2008). Studies also showed that protective wear does not only ensure protection of healthcare workers but also increase the workers’ commitment and confidence (Devi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…If there is respiratory failure early intubation should be done. 8 Women with comorbidities may have an increased risk of severe morbidity and mortality. The cycle threshold signifying the viral load and degree of infectivity can modify management during pregnancy.…”
Section: Introductionmentioning
confidence: 99%